MdGGT1 Impacts Apple miR156 Precursor Levels via Ontogenetic Changes in Subcellular Glutathione Homeostasis - Chen, Yakun; Zheng, Qingbo; Jia, Xiaolin; Chen, Keqin; Wang, Yi; Wu, Ting; Xu, Xuefeng; Han, Zhenhai; Zhang, Zhihong; Zhang, Xinzhong (Frontiers in Plant Science, 2019)
The vegetative phase change in flowering plants is controlled by microRNA156 (miR156) under transcriptional regulation. However, the developmental signals upstream of miR156 are not well understood. The glutathione/glutathione disulfide (GSH/GSSG) ratios and GSH levels decline significantly during phase change, which is consistent with miR156 expression in apple (Malus domestica Borkh.). Here, we found that the content of protein conjugated glutathione was remarkably higher in chloroplasts and nuclei of adult than juvenile phase apple hybrids. The decrease in miR156 expression was most relevant to the activities of serine acetyltransferase (SAT) and soluble γ-glutamyl transpeptidase (GGT), and the expressions of MdGGT1 or MdSATs. Transgenic apples over-expressing MdMIR156 or miR156-mimetic (MIM156) did not alter MdGGT1 expression or the soluble GGT activity. Inhibition of GGT activity with serine-borate complex or acivicin led to significant reduction in GSH content, the GSH/GSSG ratio, and the expressions of MdMIR156a5, MdMIR156a12, and miR156. Depletion of GSH with diethyl maleate without altering GGT activity caused a dramatic decrease in the expression of MdMIR156a5, MdMIR156a12, and miR156. Manipulating GGT activity and GSH homeostasis by transgenic over-expressing or RNAi MdGGT1 increased or decreased MdMIR156a5 and MdMIR156a12 levels, respectively. These data provided novel evidence that MdGGT1 participates in transcriptional level of transcription regulation of miR156 precursors during ontogenesis.